How to Adapt Mongolian Yurt to the Modern Requirements and European Climate—Airtightness versus CO2 Concentration? - Tomasz Kisilewicz; Katarzyna Nowak-Dzieszko; Katarzyna Nowak; Sabina Kuc; Ksenia Ostrowska; Piotr Śliwiński (Energies, 2021)
There are currently trends in the world to transfer and adapt traditional solutions to contemporary needs. This applies, inter alia, to mobile shelters used by nomadic peoples. The article is devoted to the research on the quality of internal air in the yurt and the possibilities of its adaptation to high contemporary quality and environmental requirements, while maintaining its characteristic sustainable values. The tested traditional Mongolian yurt was moved from the dry and cold climate of the Asian steppe to the temperate climate of Central Europe and has been significantly modified. The outer shell materials have been changed, replacing natural materials with modern tight insulating foils. The wood-fired stove has been replaced with an electric heater and the roof opening has been firmly closed. All of these modifications resulted in far-reaching changes in the quality of the internal environment in the yurt. The conducted measurements and simulations of CO2 concentration in the modified yurt proved that the efficiency of ventilation system is not sufficient and that the air quality is very poor (even for a single user). In the case of a larger number of users, the concentration of CO2 has already reached a level that was dangerous to health. The simplest method of improving the air quality in the yurt is its careful unsealing to the required level. Striving for a low energy demand, however, would require a completely different approach (for example, in the form of forced ventilation with a heat recovery unit, ultimately powered with a PV array). Such a solution is very different from the traditional yurt model but is close to modern expectations and environmental requirements.